The relationship between villous height and growth performance, small intestinal mucosal enzymes activities and nutrient transporters expression in weaned piglets. Issue 2 (14th January 2020) - Wang, Min; Yang, Chan; Wang, Qiye; Li, Jianzhong; Huang, Pengfei; Li, Yali; Ding, Xueqin; Yang, Huansheng; Yin, Yulong
Abstract: Intestinal villi are important structures for digesting and absorbing nutrients. It was hypothesized that intestinal villous height (VH) is related to growth performance, and that VH is associated with digestive and absorptive capabilities in piglets. Sixty 21‐d‐old weaned piglets were fed identical diets for 28 days. The piglets were grouped according to jejunal or ileal VH at the end of the experiment, including short, middle and high VH groups. The final BW (quadratic, p  = .003), ADG (liner, p  = .052; quadratic, p  = .030) and G: F (liner, p  = .074; quadratic, p  = .005) were greater in higher VH piglets compared with the shorter VH piglets. Significant linear relationships were recorded between jejunal VH and maltase (linear, p  = .003) and sucrase (linear, p  = .004) activities. Besides, jejunal VH was significantly associated with maltase ( r  = 0.357, p  = .007), sucrase ( r  = 0.394, p  = .003) and alkaline phosphate ( r  = 0.288, p  = .033) activities. Jejunal Slc1a1 (linear, p  = .004) mRNA expression increased as VH increased, while Slc7a1 (linear, p  = .007) expression decreased as VH increased, and Slc1a1 ( r  = 0.292, p  = .031) expression was positively related to VH. In the ileum, Slc5a1 (linear, p  = .002) and Slc1a1 (linear, p  < .001) expression increased as VH increased, whereas Slc7a1 (linear, p  = .045) expression decreased as VH increased. A positive relationship between ileal VH and Slc5a1 ( r  = 0.331, p  = .018), Slc1a1 ( r  = 0.444, p  = .001) and Slc6a19 ( r  = 0.314, p  = .026), respectively, was established. Additionally, Slc7a9 ( r  = 0.0271, p  = .057) expression tended to be positively associated with VH in ileum. In conclusion, the growth performance of piglets increased with increasing VH, which may via affecting mucosal enzymes activities and nutrient transporters' mRNA expression.